2001
DOI: 10.1103/physrevlett.87.197003
|View full text |Cite
|
Sign up to set email alerts
|

Critical Dynamics of a Vortex-Loop Model for the Superconducting Transition

Abstract: We calculate analytically the dynamic critical exponent zMC measured in Monte Carlo simulations for a vortex loop model of the superconducting transition, and account for the simulation results. In the weak screening limit, where magnetic fluctuations are neglected, the dynamic exponent is found to be zMC = 3/2. In the perfect screening limit, zMC = 5/2. We relate zMC to the actual value of z observable in experiments and find that z ∼ 2, consistent with some experimental results.PACS Numbers: 05.70.Jk, 74.40.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This value of z was found previously by other experimental groups 7,74 and elaborated on theoretical grounds. 85 However, alternative values for the dynamical critical exponent have also been quoted in the literature. 9,10 Recently, it has been shown that the original experimental results in thin films can be analyzed properly only by accounting for the finite size effects and the value of z then extracted.…”
Section: Analysis Of the Complex Conductivity Due To Superconductimentioning
confidence: 99%
“…This value of z was found previously by other experimental groups 7,74 and elaborated on theoretical grounds. 85 However, alternative values for the dynamical critical exponent have also been quoted in the literature. 9,10 Recently, it has been shown that the original experimental results in thin films can be analyzed properly only by accounting for the finite size effects and the value of z then extracted.…”
Section: Analysis Of the Complex Conductivity Due To Superconductimentioning
confidence: 99%